Insulin-like factor 3 as a monitor of endocrine disruption - Anand-Ivell, Ravinder; Ivell, Richard (Society for Reproduction and Fertility, 2014)
Insulin-like factor 3 (INSL3) is generated and secreted by differentiated interstitial Leydig cells of the testes in both fetal and adult males of all mammalian species so far analyzed. All evidence to date suggests that it is produced constitutively, independently of acute regulation by the hypothalamo-pituitary–gonadal (HPG) axis, in amounts which reflect the numbers and differentiation status of the Leydig cells. This Leydig cell functional capacity is otherwise monitored only by androgen output, which, however, is massively confounded by acute regulation from the HPG axis and other factors leading to substantial and irregular short-term variation. Leydig cells are a primary target of endocrine-disrupting agents in the context of the testicular dysgenesis syndrome in the fetal male, as well as in the adult. In the male fetus, INSL3 is responsible for the first phase of testicular descent, and hence is directly linked to the etiology of cryptorchidism. In this study, by measuring INSL3 production, for example, during fetal life via amniotic fluid, or as secretions from fetal testis explants, or in adult peripheral blood, we and others have shown that INSL3 represents a useful quantitative and sensitive endpoint for assessing the impact of endocrine-disrupting agents and their mechanisms of action.